Electrochemical sensing of the behaviour of oligonucleotide lipoplexes at charged interfaces - Piedade, J. A. P. (2004)
Complexes between short oligodeoxynucleotides (ODN) with a variable dGxdCy base composition and liposomes composed of the cationic lipid DOTAP (ODN lipoplexes) were studied by differential pulse voltammetry at a glassy carbon electrode. Since lipoplexes are spontaneously formed by electrostatic interactions, the objective of the voltammetric study was to investigate their behaviour at the electrode surface/solution interface. It was verified that the peak current in the voltammograms for ODN lipoplexes was due to guanosine oxidation and that it was influenced both by the applied adsorption potential and the lipoplex (±) charge ratio used. It was found that for low ODN lipoplexes (±) charge ratios the peak current obtained was enhanced when compared to that registered with free ODN for the same concentration. This allowed a higher sensitivity in the determination of ODN by differential pulse voltammetry and a limit of detection of 5.5 ng/mL was achieved. A model that explains the organisation of ODN lipoplexes at the electrode surface/solution interface is proposed. The electrochemical results presented account for a better physicochemical characterisation of lipoplexes at charged interfaces, which can be important for the understanding and development of gene therapy vectors based on ODN lipoplexes.